USING COMPUTER TECHNOLOGY IN INTERSUBJECT PROJECTS OF PHYSICS DURING THE STUDY PRACTICE (Journal of Information Technologies in Education (ITE), 2010)
This article discusses the use of computer technology in the performance of students in physics interdisciplinary projects during the academic practice.
Keywords: computer technology; educational practice; intersubject projects